A Coding Algorithm using Super-edge Magic Total Labeling of Extended Duplicate Graphs - Jegan, R.; Vijayakumar, P.; Thirusangu, K. (2022 Second International Conference on Computer Science, Engineering and Applications (ICCSEA), 2022)
Graph labeling has wide applications in the field of radio astronomy, computer networks, communication networks and cryptography etc. Encoding is a technique of sending messages as codes over a communication channel decoding is a method of interpreting the received codes into messages again so that only sender and receiver understands the message and others could not. Graph labeling is an assignment of labels (numbers) to vertices or edges or both subject to certain criteria. In this paper, encoding and decoding algorithms sandwiching super-edge magic total labeling algorithms, super-edge antimagic total labeling and algorithms like affine-cipher and RSA algorithms are presented to encode messages and decode codes and illustrate them with examples.